#### Question

Solve for x and y: `[(x + y, x - 4)][(-1, -2),(2, 2)] = [-7, -11]`

#### Solution

`[(x + y, x - 4)][(-1, -2),(2, 2)] = [(-7, -11)]`

`[(-x -y + 2x - 8, -2x - 2y + 2x - 8)] = [(-7, -11)]`

`[(-y + x - 8, -2y - 8)] = [(-7, -11)]`

Comparing the corresponding elements, we get

`-2y - 8 = -11 => -2y = -3 => y = 3/2`

`-y + x - 8 = -7`

`=> -3/2 + x - 8 = -7`

`=> x = 1 + 3/2 = 5/2`

Is there an error in this question or solution?

Solution Solve for X and Y: [(X + Y, X - 4)][(-1, -2),(2, 2)] = [-7, -11] Concept: Multiplication of Matrix.